ChemInform Abstract: Selective Access to All Four Diastereomers of a 1, 3‐Amino Alcohol by Combination of a Keto Reductase‐ and an Amine Transaminase‐Catalyzed Reaction. Issue 40 (October 2015) - Kohls, Hannes; Anderson, Mattias; Dickerhoff, Jonathan; Weisz, Klaus; Cordova, Armando; Berglund, Per; Brundiek, Henrike; Bornscheuer, Uwe T.; Hoehne, Matthias
Abstract The synthetic pathway to obtain the (2R, 4R)‐enantiomer (III) is outlined.